(3YQV hJMdjd hfbOs - (3eMeO MGeO(B, (3YHO Gddgs ((3GdQjGV(B:s (3YeGOI TDhf GdecJHGJ(B,s, 1987)
(3GdfXGe GdEbJUGOj hCSS Jbhjeg(B- (3GdfXGe GdEbJUGOj GdQCSeGdj(B- (3fXGe GdJNWjW GdeQcRj(B- (3GdfXGe GdEbJUGOj GdeNJdW(B- (3GdfXe GdEbJUGOjI aj GdOhd GdfGejI(B.s
Keywords: (3GdEbJUGOs; (3GdEbJUGO GdeYGUQs; (3GdfXe GdEbJUGOjIs